AGAMA DAN PERUBAHAN SOSIAL: MENDORONG KESETARAAN GENDER DALAM KONTEKS KEAGAMAAN DAN MASYARAKAT KONTEMPORER - SUGENG DWI HARIANTO; khusnul khotimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the modern era, gender equality has become one of the social issues receiving significant attention worldwide. Social changes driven by globalization, urbanization, and technological advancements have created opportunities for increased awareness of human rights and the importance of equality in various aspects of life. This study employs a qualitative method through literature review. Islamic perspectives on gender roles are diverse, with fundamental principles supporting equality between men and women, although traditional interpretations often position men as leaders and women as homemakers. Some progressive interpretations emphasize that both genders complement each other in various roles, opening space for a more inclusive gender equality. Religion holds great potential to drive social change by promoting values of justice and compassion, and by advocating for the rights of women and gender minority groups. However, challenges arise from the resistance of conservative groups that uphold traditional gender roles and patriarchal cultural norms, which hinder the implementation of gender equality in society. To overcome these obstacles, more open dialogue and a fairer social system are needed. Keywords: Religion; Gender Equality; Contemporary Society.